THE "COSH" OR SYMMETRIZED WOODS-SAXON NUCLEAR POTENTIAL - Grypeos, M. E.; Lalazissis, G. A.; Massen, S. E.; Panos, C. P. (HNPS Advances in Nuclear Physics, 2020)
The so-called "cosh" or symmetrized Woods-Saxon potential which has been used in nuclear physics is discussed and certain comments are made regarding its form-factor, depth and radius. A rough estimate of its parameters is also attempted by using various possibilities. This is done by considering either a number of individual nuclei or by least squares fitting. The potential depth parameter Vo apart from being state dependent varies also with the mass number of the nucleus. Comments on relevant limitations and inaccuracies are also made.